Theory And Application Of Magneto-Optic Techniques In The Non Contact Measurement Of Current - Munusamy, Narayanan (Universiti Sains Malaysia, 2005)
Although the use of semiconductor magnetic sensors and fiber optical devices for making quantitative industrial controls, navigation systems, medical imaging and land-mine detection have been long established. There exists a body of other measurement capabilities for such devices, which have gone generally unnoticed. These involve measurement of current, charge carrier, magnetic flux, voltage and power which may be generally referred to as electrical quantities. The semiconductor magnetic sensors used to detect changes in current as big as 10.0A and on the other hand, the photo detector used to detects changes in light due to the variation of current as small as 1.0mA. Because of the measurement occurs contact less and a high temporal resolution is achievable, this sensor and optical techniques can open up a new perspectives in the field of real-time production metrology, for example controlling DC motor or a chemical process with saves in consuming time, manpower and money.